Clinical and equipment-related factors associated with the adequate peripheral blood stem cell collection in autologous transplant at a tertiary cancer center in Kerala - A retrospective cohort study. (August 2019) - Murugesan, M; Shringarpure, K; Karthickeyan, D.S.A; Nair, C.K; Nayanar, S.K; Venugopal, V; Selvaraj, K; Rathi, P; Mehta, K.G; Deenathayalan, V; Gayathiri, K.C
Abstract: Background: PBSC collection using apheresis is the preferred source of hematopoietic stem cells transplantation. However, apheresis procedures fail to harvest adequate CD34 yield in 5 to 40% of patients during the first collection. Therefore, this study aimed to study both the clinical- and equipmentrelated factors influencing CD34 yield among the autologous patients and to compare the collection efficiency of two apheresis equipments(Haemonetics MCS+ and Terumo Spectra Optia). Methods: Retrospective analysis of 69 patients underwent PBSC collection from 2015 to 2018. Frequency, clinical- and equipment-related factors responsible for adequate CD34+ cells (≥2 x106 cells/kg) yield during the first collection was studied. Factors such as collection efficiency, percentage platelet loss and percentage hemoglobin loss were considered to compare the two apheresis system. Results: Two-third (72%) patients of the study population had adequate CD34 stem cells yield during the first collection. Factors such as exposure to lenalidomide-based pretreatment regimen, peripheral blood WBC count and CD34 count are associated with the adequate CD34 yield. Optia had a slightly better collection efficiency than MCS+ (50 and 44; p=0.37). Optia had lower product volume (237 vs 298 ml) and lesser procedure duration (277 vs 360 min), whereas the median Hb loss (3.0% and 2.3%) and mean platelet loss (49% and 34%) were higher with MCS. Conclusion: This study infers that the collection efficiency of both the equipments in collecting CD34 stem cells was similar. However, during PBSC collection, procedures using Optia can be preferred to MCS+ on the patients with risk of anemia and thrombocytopenia.